CaMKII Requirement for in Vivo Insular Cortex LTP Maintenance and CTA Memory Persistence - Juárez-Muñoz, Yectivani; Ramos-Languren, Laura E.; Escobar, Martha L. (Frontiers in Pharmacology, 2017)
Calcium-calmodulin/dependent protein kinase II (CaMKII) has an important role in LTP induction, but since it has the capacity to remain persistently activated even after the decay of external stimuli it has been proposed that it can also be necessary for LTP maintenance and therefore for memory persistence. It has been shown that basolateral amygdaloid nucleus (Bla) stimulation induces long-term potentiation (LTP) in the insular cortex (IC), a neocortical region that has been related with acquisition and retention of conditioned taste aversion (CTA). Our previous studies have demonstrated that induction of LTP in the Bla-IC pathway before CTA training increased the retention of this task. Although it is known that IC-LTP induction and CTA consolidation share similar molecular mechanisms, little is known about the molecular actors that underlie their maintenance. The aim of the present work was to evaluate the role of CaMKII in the maintenance of in vivo Bla-IC LTP as well as in the persistence of CTA long-term memory (LTM). Our results show that acute microinfusion of myr-CaMKIINtide, a selective inhibitor of CaMKII, in the IC of adult rats during the late-phase of in vivo Bla-IC LTP blocked its maintenance. Moreover, the intracortical inhibition of CaMKII twenty-four hours after CTA acquisition impairs CTA-LTM persistence. Together these results indicate that CaMKII is a central key component for the maintenance of neocortical synaptic plasticity as well as for persistence of CTA-LTM.